Media Scholarship in a Transitional Age: Research in Honor of Pamela J. Shoemaker - Liebler, Carol M. and Vos, Tim P. (Mass Communication and Journalism Series, 2018)
Media Scholarship in a Transitional Agehonors the significant and lasting contribution that Pamela J. Shoemaker has made to mass communications research. A collection with wide appeal to all media scholars, this book is particularly well suited to graduate student seminars on mass communications theory, media sociology and news scholarship.
https://katalog.adlr.link/Record/76-EBC5317026